2014
DOI: 10.1002/j.0022-0337.2014.78.4.tb05714.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Instructional Methods: Oral and Pharyngeal Cancer Examination

Abstract: This study compared the effectiveness of different methods of instruction for the oral and pharyngeal cancer examination. A group of thirty sophomore students at the University of Florida College of Dentistry were randomly assigned to three training groups: video instruction, a faculty-led hands-on instruction, or both video and hands-on instruction. The training intervention involved attending two sessions spaced two weeks apart. The irst session used a pretest to assess students' baseline didactic knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The results of this study indicate a major disconnect between knowledge and actual practice. These results are concerning as it is known that early detection of oral cancer is a critical factor for improving survival rates . There is evidence to suggest that increased regularity of dental examinations is associated with earlier stage at diagnosis for oral and pharyngeal cancer so efforts should be made to screen for oral cancer during recall examinations .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study indicate a major disconnect between knowledge and actual practice. These results are concerning as it is known that early detection of oral cancer is a critical factor for improving survival rates . There is evidence to suggest that increased regularity of dental examinations is associated with earlier stage at diagnosis for oral and pharyngeal cancer so efforts should be made to screen for oral cancer during recall examinations .…”
Section: Discussionmentioning
confidence: 99%
“…The self‐reports are often based on a perception that a visual examination constitutes oral cancer screening and are not based on a uniform definition of a comprehensive examination . Several studies have shown that dentists and dental hygienists are looking for lesions; however, it must be emphasized that visual examinations are considered partial examinations and intra/extra‐oral examinations must include both a visual and tactile component otherwise abnormalities can easily be missed . The fact that only partial examinations are more commonly performed can be attributed to a need for further education on oral cancer screening and/or a need to extend appointment times so that screenings can be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has shown that educational movies based on However, Clark [9], stated that students performed signifi cantly better in the combination of video and faculty-ledhands-oninstruction than video or instruction alone regarding oral and pharyngeal cancer examination. Weber [10], concluded that video-based instruction is a more effective teaching method than conventional instruction for learning surgical hand disinfection.…”
Section: Answering the Main Research Questionmentioning
confidence: 82%
“…Fourteen of the 21 studies involved the examination of pre-doctoral dental students' readiness to assess risks for OPC, 6,[10][11][12][13][14][18][19][20][21][22][23]25,27 but only one study discussed training material content for their curriculum. 27 Another single study even highlighted that dental students in their final year appeared more knowledgeable on risk factors and clinical aspects of OPC as a result of the undergraduate dental curriculum. 10 A further study even described dental students' perspectives around discomfort in discussing sexual-related topics 23 and the necessity for structured learning for assessing HPV as a risk factor with patients.…”
Section: Assessing Risk Factors For Opc and Hpvmentioning
confidence: 99%